Clinical Time Savings and Experiences Using a Business-to-Customer Model for Cochlear Implant Sound Processor Upgrades - Jane Bradley MSc; Wendy J. Huinck PhD; Angella Fuller BSc; Martin O’Driscoll PhD; Lorna Whitehouse MSc; Andrew Soulby MSc; Paula Greenham MSc (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
This study assesses the implementation and time savings associated with an innovative business-to-customer model (B2C) for the remote application of sound processor upgrades, a task related to ongoing cochlear implant maintenance. The upgrade to recipient model (U2R) involves the transfer of patient data to a cloud where the company that supplies the upgraded processor can upload it into the devices and dispatch them directly to the patient. It replaces the traditional face to face model, requiring patients to come into the clinic. Four clinics in the U.K. and one in the Netherlands were surveyed on their experiences and satisfaction levels after implementing this model. The time saved when using the U2R model was compared to the time taken for a face-to-face appointment. Upgrades were done using the U2R model in 43% of adults and children. Time savings ranged between 21 and 65 minutes per patient. Although patients were reported to be satisfied with the service, up to 50% of U2R patients requested a further in clinic follow up appointment. Four out of five clinics were satisfied with the current U2R model and would recommend it to another clinic. The other clinic required modifications to the administration of the model. Large savings in clinic and patients costs and time were reported. Streamlining the process within clinics and providing better remote support for patient reassurance and to solve equipment issues at home would ensure that time savings are maximised and the B2C model provides comparable quality to an in-clinic appointment.